The effect of ownership structure on dividend policy (An applied study on companies listed on the Damascus Securities Exchange) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This research aims to shed light on the impact of the ownership structure of companies listed in Damascus Securities Exchanges on the dividend policy adopted by these companies during the period (2010-2019) to achieve this objective, the two researchers used a hypothetical-deductive approach to formulate the hypotheses; and analyzed the financial statements of all companies listed in Damascus Securities Exchanges. The results of the study showed that there is an impact of the following ratios (percentage of ownership of Syrian retail investors RI_S, percentage of ownership of foreign retail investors RI_F, number of independent Arab board members IN_A_BM, percentage of return on equity, size of the company) on the Stock dividend, as shown The results have an effect for each of the following ratios (percentage of ownership of retail investors RI, ownership percentage of foreign retail investors RI_F, debt ratio DR, size of the company) on the cash dividends DPR.